Assosiation Of Metabolic Syndrome And Female Pattern Hair Loss - ضاما, رغد; رولا بدور; فيصل رضوان (Latakia University Journal -Medical Sciences Series, 2024)
Background: Female pattern hair loss may be associated with several disease such as high blood pressure ,hyperandrogenism and pcos and these women may have high cholesterol levels and increased risk of late onset of diabetes. Aim:.this study aims to investigate the relationship between FPHL and the chronic metabolic abnormalitis (Metabolic syndrome diagnosed according to the Adult Treatment Panel-III criteria) Materials and Methods: This study was conducted in the department of dermatology, Tishreen university, Lattakia, Syria. The study included 50 patients and 50 controls, matched in age and sex. Abdominal circumference (WC) and blood pressure(SBP,DBP) were measured. Fasting serum concentration was measured for each of FBG, HDL, TG. Results: Metabolic syndrome was diagnosed in 15 patients with FPHL(30%) compared with 6 control subjects(12%) (P= 0.031). The most common feature in the patients was an increased: waist circumference in patients compared with control (50% compared with 26% pvalue<0.05) Blood pressure (Systolic or diastolic 34% versus 14% p value<0.05) with decreased in HDL level (58% versus 38%) (P<0.05). There was no significant difference in FBG (18% versus 12% p>0.05 ) Triglycerides (24% versus 12% p>0.05 ) between patients and controls. Conclusion We demonstrated a significant association between MetS and FPHL. Women with FPHL, particularly with the high severity of the disease, should be screened for MetS criteria for early identification and management.